vibroacoustic, structure-borne, respons dinamik transien, sound pressure level (SPL) - Muhammad Said, Rizki
Light Rail Transit (LRT) is one of transportation option which built for connecting the suburban to the city centre safely and comfortable. for realizing it, many railway technology developed especially in performance aspect which covers emission, power, and the most important one is noise, vibration, and harshness aspect (NVH). These aspects become important remembering that in Jakarta, Bogor, Depok, and Bekasi (Jabodebek) there are many transportation mode exist so if LRT Jabodebek is not comfortable, the passenger would leave it. This undergraduate thesis discuss about the prediction of vibration and interior noise performance of the LRT Jabodebek due to track irregularity excitation and velocity variation. The process begins by multibody dynamics modeling for obtaining the connector acceleration between carbody and bogie part. The data then will be used for input in finite element model for analyzing vibration and acoustic performance. The result shows that by increasing the track irregularity or rail vehicle velocity, the floor vibration level and the sound pressure level will be increased as well. Moreover, the noise level produced by track irregularity excitation is in non-audible domain.